EVALUASI KUALITAS PELAYANAN JUAL BELI HANDPHONE BERBASIS INTEGRASI METODE SWOT DAN QSPM - Renaldy Eka Ramadhan; Nina Aini Mahbubah (SIGMA TEKNIKA, 2022)
The widespread use of mobile phones has gained opportunities for the services business. B-CELL is a small-sized firm that sells and buys cellphones, prepaid top-ups, cellphone accessories, and cellphone services. Similar businesses around the area resulted in challenging competition. This study aims to evaluate the internal and external factors of the B-Cell service business and determine the priority of marketing strategies based on the integration of the SWOT and QSPM approaches. The results of this study identified that the strength factor with the highest weight was a reasonably strategic location and fast and friendly service. Furthermore, the highest weight weakness factor is the poor distribution ability. For the opportunity factor, the highest weight is the quality of products recognized by consumers and high consumer demand. It was found that the threat factor with the highest weight was innovation in marketing, and marketing strategies were required to always be up-to-date in providing information to consumers. SWOT matrix shows that the SO strategy is to meet market demand, improve service quality, and market products using online media. The WO strategy includes providing pre-order systems, expanding supplier selection criteria, and improving facilities and the quality of Human Resources. ST strategy includes routinely conducting market research and improving service quality and Human Resources. WT's strategy is to conduct market research for innovations and improve the quality of human resources by conducting training. The marketing strategy recommendation based on the QSPM with the highest ranking is to regularly research market desires. The lowest rank is to innovate the right marketing strategy.